Investigating the ameliorative potential of Aspalathus linearis and Cyclopia intermedia against lipid accumulation, lipolysis, oxidative stress and inflammation - Mamushi, Mokadi Peggy (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.